Profile of Tofacitinib in the Treatment of Ulcerative Colitis: An Evidence-Based Review of Recent Data - Varyani F; Argyriou K; Phillips F; Tsakiridou E; Moran GW (Dove Medical Press, 2019)
Fumi Varyani,1,* Konstantinos Argyriou,2,* Frank Phillips,1,* Eirini Tsakiridou,3 Gordon William Moran2,4 1Queen’s Medical Center, Nottingham University Hospitals NHS Trust, Nottingham, UK; 2Nottingham Digestive Diseases Centre, School of Medicine, University of Nottingham, Nottingham, UK; 3University Hospital of Athens “LAIKO”, Athens, Greece; 4National Institute of Health Research, Nottingham Biomedical Research Centre at Nottingham University Hospitals National Health Service Trust and the University of Nottingham, Nottingham, UK*These authors contributed equally to this workCorrespondence: Konstantinos ArgyriouNottingham Digestive Diseases Centre, Room W/E West Block, Queen’s Medical Centre, Nottingham NG7 2UH, UKEmail kosnar2@yahoo.grAbstract: Recent advances in the understanding of the pathophysiology of ulcerative colitis (UC) have led to the expansion of our therapeutic arsenal. Conventional treatment options, including aminosalicylates, corticosteroids, thiopurines, and calcineurin inhibitors, fail to control the disease in a significant proportion of patients. Approximately 25–50% of the patients treated with tumor necrosis factor antibodies (anti-TNFα) are primary and secondary non-responders to therapy. Tofacitinib is a novel orally administered small synthetic molecule that inhibits a homologous family of enzymes, termed Janus kinases that modulate multiple key cytokines involved in the pathogenesis of UC. Phase II and III trials showed promising results in UC, leading the Food and Drug Administration (FDA) and the European Medicines Agency (EMA) to approve its administration for the induction and maintenance of remission in moderate-to-severe UC. Herein, we review tofacitinib for the management of UC, its mechanism of action pharmacokinetic properties, efficacy, and safety.Keywords: tofacitinib, ulcerative colitis, Janus kinase inhibitors, Jakinibs